Bioinformatics-based analysis of the roles of basement membrane-related gene AGRN in systemic lupus erythematosus and pan-cancer development - Lv, Rundong; Duan, Lei; Gao, Jie; Si, Jigang; Feng, Chen; Hu, Jun; Zheng, Xiulan (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease involving many systems and organs, and individuals with SLE exhibit unique cancer risk characteristics.The significance of the basement membrane (BM) in the occurrence and progression of human autoimmune diseases and tumors has been established through research.However, the role of BM-related genes and their protein expression mechanisms in the pathogenesis of SLE has not been elucidated. In this article, we performed differential expression analysis of BM-related genes on datasets of SLE patients, used LASSO logistic regression, SVM-RFE, and RandomForest to analyze these differentially expressed BM-related genes, and screened six feature genes (AGRN, PHF13, SPOCK2, TGFBI, COL4A3, and COLQ) to construct an SLE diagnostic model. In order to attain a comprehensive comprehension of the biological functionalities of the feature genes, we conducted GSEA analysis, ROC analysis, and computed levels of immune cell infiltration. The results revealed a significant association between AGRN and immune cell functions such as parainflammation and type I IFN response. Consequently, we sourced pan-cancer expression profiles from the TCGA databases and subjected AGRN to a further prognosis analysis in pan-cancer tissues, evaluating its correlation with the tumor microenvironment. The pan-cancer analysis disclosed that AGRN's expression level varied according to distinct tumor types and was closely correlated with some tumor patients' prognosis, immune cell infiltration, and other indicators. In conclusion, BM-related genes play a pivotal role in the pathogenesis of SLE, and AGRN shows immense promise as a target in SLE and the progression of multiple tumors.